A three-armed cognitive-motor exercise intervention to increase spatial orientation and life-space mobility in nursing home residents: study protocol of a randomized controlled trial in the PROfit project - Bettina Wollesen; Madeleine Fricke; Carl-Philipp Jansen; Katharina Gordt; Michael Schwenk; Thomas Muehlbauer; Christina Morawietz; Adele Kruse; Klaus Gramann (BMC Geriatrics, 2020)
Abstract Background In nursing home residents, the combination of decreasing mobility and declining cognitive abilities, including spatial orientation, often leads to reduced physical activity (PA) and life-space (LS) mobility. As a consequence of sedentary behavior, there is a lack of social interaction and cognitive stimulation, resulting in low quality of life. It has not yet been examined whether cognitive-motor training including spatial cognitive tasks is suitable to improve spatial orientation and, as a consequence, to enlarge LS mobility, and increase well-being and general cognitive-motor functioning. Therefore, the overall goal of this multicentric randomized controlled trial (RCT) is to compare the effect of three different intervention approaches including functional exercise and orientation tasks on PA, LS and spatial orientation in nursing home residents. Methods A three-arm single-blinded multicenter RCT with a wait-list control group will be conducted in a sample of 513 individuals (needed according to power analysis) in three different regions in Germany. In each nursing home, one of three different intervention approaches will be delivered to participating residents for 12 weeks, twice a week for 45 min each: The PROfit basic group will perform functional strength, balance, flexibility, and walking exercises always at the same location, whereas the PROfit plus group changes the location three times while performing similar/the same exercises as the PROfit basic group. The PROfit orientation group receives navigation tasks in addition to the relocation during the intervention. Physical and cognitive functioning as well as psychological measures will be assessed in all study groups at baseline. Participants will then be randomized into either the intervention group or the wait-list control group. After 12 weeks, and after 24 weeks the measures will be repeated. Discussion This study evaluates whether the three different interventions are feasible to reduce the decline of or even improve PA, LS, and spatial orientation in nursing home residents. By adding different training locations in PROfit plus, the program is expected to be superior to PROfit basic in increasing physical and cognitive parameters. Moreover, we expect the PROfit orientation intervention to be most effective in terms of PA, LS, and spatial orientation due to two mechanisms: (1) increased physical and cognitive activity will enhance cognitive-motor capacity and (2) the spatial training will help to build up cognitive strategies to compensate for age-related loss of spatial orientation abilities and related limitations. Trial registration The trial was prospectively registered at DRKS.de with registration number DRKS00021423 on April 16, 2020 and was granted permission by the Technical University Berlin local ethics committee (No. GR_14_20191217).